Analisis Keberlanjutan Pengusahaan Rumah Walet dalam Kontribusinya Pembangunan di Provinsi Banten - Arum Kusnila Dewi; Muhammad Saleh S. Ali; Imam Mujahidin Fahmid; Sudirman Baco (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Sustainable development is development aimed at achieving a better quality of life. The sustainability of swiftlet bird nest (SBN) exports is influenced by the quality of swiftlet house production. Banten Province is a producer and supplier of high-quality SBN for export and local markets. Analysis of swiftlet house business sustainability encompasses three aspects: the ecological, economic, and social aspects. The sample consisted of thirty-eight (38) swiftlet houses in the coast, hills, and plains ecological areas located in the regencies of Banten Province. The analysis used was the RAPFISH (Rapid Appraisal for Fisheries) method which is an analysis tool or method based on Multidimensional-Scaling (MDS) through the R Software program. MDS is a statistical technique through multidimensional transformation into a lower dimension for measuring sustainability. The levels of sustainability on the coast, hills, and plains are 53.16%, 55.44%, and 56.94%, respectively. A value greater than or equal to 50% indicates a sustainable status; thus all these areas have a sustainable status. The determination of sensitive attributes was measured based on the priority order of the results of the MDS leverage analysis by observing the form of changes in the Root Mean Square (RMS). The greater the RMS value, the more significant the role of the attribute in influencing the sustainability of swiftlet house management. The highest RMS value impacting the success of swiftlet house management based on the ecological aspect is the threat of losses due to pests and disease outbreaks. This is also an economic factor with the highest value and is quite crucial. The existence of pests is closely related to the ecological aspect that leads to economic loss. The social aspects influencing sustainability are coordination between institutions and standardized public services. Coordination has the highest level of sensitivity which shows that synergy between institutions plays an important role in swiftlet house management. Good coordination can assist in the formulation of policies, implementation of effective regulations, and integrated supervision.